State Martyr Representation and Performativity of Political Violence - Scolari, Baldassare (Media and Religion / Medien und Religion, 2019)
Politician Aldo Moro was abducted and killed in 1978 by the terrorist organization Red Brigades. The media then stylized Moro as a «state martyr». The volume deals with the highly topical question concerning the performativity of this concept in the tension between democratic state and terrorism and reconstructs a crucial phase of post-war time policy in Italy on the basis of media sources on the Moro case. What performs a term from Christian antiquity within modern socio-political discourses? What changes has the term "martyr" undergone in European religious and cultural history? On the basis of these questions, the study opens up an interdisciplinary theoretical horizon to understand the role of religious motives in socio-political con-texts. It brings a central new dimension to the secularization debate, which sees secularization as a new configuration of politics and religion.